Creative lifeworld in Geriana Kauh Village; Intertwining of culture and nature during the pandemics in Bali - Putri, LG. Saraswati (UI Scholars Hub, 2022)
This research is an attempt to delve into understanding the process of creative imagination of the sacred which is revealed in the intertwining of culture and nature in Geriana Kauh, Karangasem, Bali. This study aims to investigate the relationship between the individual, the social and ecology, as well as the transformation of individual consciousness into a collective awareness sharing a communal reality. This qualitative research is developed by incorporating theoretical analysis and formulating field data collected in the traditional Village of Geriana Kauh, as the villagers resort to their cultural resources to deal with the cosmological imbalances caused by pandemics. By means of a phenomenological examination, this investigation underlines the dynamic interlocking of the cultural and the natural worlds.